Beyond projects: benefits of research accompanying research. Reflections from the research programme Sustainable Land Management. - Weith, Thomas; Rogga, Sebastian; Zscheischler, Jana; Gaasch, Nadin (Oekom, 2019)
In manifold ways science and practice are working together to find solutions for sustainable land management. New research programmes an this topic generate a large variety of single project results. Accompanying research projects will realize additional value by merging and synthesising the results from these projects and by supporting the generation of new knowledge for science and society.
Keywords: Ländlicher Raum; Raumforschung; Landmanagement; Landschaftsentwicklung; Ländliche Entwicklung; Nachhaltigkeit; Forschung; Klimawandel; Ökosystem; Wissenstransfer; Transdisziplinarität